Microbiological evaluation of Minas artisanal cheese from the Pontal do Triângulo Mineiro region (Research, Society and Development, 2023)
In Brazil, the production of artisanal cheeses made from raw milk is expressive and the process has been passed down from generation to generation. Currently, Minas Gerais has a total of 10 microregions characterized as producers of artisanal minas cheese (QMA). The Pontal do Triângulo Mineiro Region is claiming the characterization of the Pontal do Triângulo Mineiro micro-region. In contribution to the claim of characterizing this micro-region, the objective of this work was to characterize samples of cheese from the region of Pontal do Triângulo Mineiro. Microbiological analyzes were carried out (coliforms at 35 ºC, Escherichia coli, Staphylococcus aureus, Listeria monocytogenes and Salmonella) of artisanal Minas cheese samples from 4 producers in Pontal do Triângulo Mineiro at 5 different maturation periods (01, 08, 15, 20 and 22 days), with two repetitions of the experiment. The results of the microbiological analyzes indicated, in the analyzed samples, that the microbiological parameters, mainly in the rainy season, did not meet the minimum required by the current legislation.